2009
DOI: 10.1007/s10616-009-9235-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pretreatment or combined treatment of quercetin on menadione toxicity in rat primary mixed glial cells in vitro

Abstract: Neurons and glia are highly susceptible to reactive oxygen species that play a key role in various neurodegenerative diseases. Menadione, a synthetic derivative of vitamin K, induces reactive oxygen generation. Quercetin one of the most ubiquitous bioflavonoids in food of plant origin, has strong antioxidant activities on different cell types, however recent studies demonstrated that it has also prooxidant and cytotoxic potentials. We examined the action of pre- and co-treatment of quercetin on menadione induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Recent studies have indicated that the oxidative stress develops when the levels of antioxidants are lowered (Tapiero et al 2004;Banudevi al. 2005;Oztopcu-Vatan et al 2009). Individual antioxidants can be considered very sensitive in revealing a pro-oxidant challenge (Regoli and Winston 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that the oxidative stress develops when the levels of antioxidants are lowered (Tapiero et al 2004;Banudevi al. 2005;Oztopcu-Vatan et al 2009). Individual antioxidants can be considered very sensitive in revealing a pro-oxidant challenge (Regoli and Winston 1999).…”
Section: Discussionmentioning
confidence: 99%
“…A study in HepG2 cells reported that quercetin might exert dose-dependent cytoprotective and cytotoxic effects 7 . It has been reported that low concentrations and short-term administration of quercetin have antioxidant and anti-apoptotic effects, and at high concentrations, it disrupts the antioxidant defense system, causing oxidative damage and increasing apoptosis [31][32][33] . As a result, the effect of quercetin may vary according to concentration, application time, applied cell type or culture conditions, and contradictory effects may be seen at the same time.…”
Section: Discussionmentioning
confidence: 99%